2023
DOI: 10.1177/15344843221148044
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Rich Pictures’ Method: Its Use and Value, and the Implications for HRD Research and Practice

Abstract: Embracing new and innovative qualitative methods has helped researchers in a number of fields to access aspects of the lived experience that traditional methods cannot easily reach. This paper explores the use and value of one such method – ‘rich pictures’: a technique whose origins lie in ‘soft systems’ engineering but which has been successfully applied in a broader range of contexts in recent years including health, medicine and education. Despite its use in these disciplines, however, recent studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…The first activity invited participants to reflect upon the question "what does fire mean to you?". Rich pictures are an epistemological constructivist approach that acknowledge diversity in our understandings of a specific issue based on previous experiences and background knowledge [85]. Participants were asked to illustrate their individualistic interpretation of the question using drawings, symbols, and text [86].…”
Section: Rich Picturesmentioning
confidence: 99%
“…The first activity invited participants to reflect upon the question "what does fire mean to you?". Rich pictures are an epistemological constructivist approach that acknowledge diversity in our understandings of a specific issue based on previous experiences and background knowledge [85]. Participants were asked to illustrate their individualistic interpretation of the question using drawings, symbols, and text [86].…”
Section: Rich Picturesmentioning
confidence: 99%
“…We set out at the start of this paper with two questions: ‘What are the affordances and constraints of using Rich Pictures to uncover tacit perspectives?’ and ‘Moving forward, how can we most effectively use Rich Pictures in future research?’ From our research and the literature on Rich Pictures we have identified that the affordances are that firstly, Rich Pictures allow people to think in a non-linear way to reveal tacit perspectives and depict emotions, relationships, culture and context in complex social situations (Cristancho, 2015; Cristancho & Helmich, 2019; Gisby et al, 2023). Second, they can be used in a variety of cultural contexts or situations where verbal interactions may be difficult (Amazonas et al, 2019; Bell et al, 2016b) and third they allow participants the space and time to reflect and draw about complex social situations which provides the researcher with more nuanced perspectives around the phenomenon being investigated (Bood et al, 2019; Helmich et al, 2018).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Second, they can be used in a variety of cultural contexts or situations where verbal interactions may be difficult (Amazonas et al, 2019; Bell et al, 2016b) and third they allow participants the space and time to reflect and draw about complex social situations which provides the researcher with more nuanced perspectives around the phenomenon being investigated (Bood et al, 2019; Helmich et al, 2018). However, as with any method, there are constraints to the Rich Picture method, namely that participants often feel reluctant to draw due to their perceived lack of artistic ability and that the time to reflect and draw may place a heavy burden on participants (Cristancho & Helmich, 2019; Gisby et al, 2023). The benefits need to outweigh the costs for both researcher and participant.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations